PROSPECTIVE SOCIAL STUDIES TEACHERS' PERCEPTIONS ON THE CONCEPT OF "CITIZEN(SHIP)" - Oğuzhan KARADENİZ; Fatih KAYAALP; Esma Nur KARAMEŞE (International Journal of Eurasia Social Sciences, 2018)
The concept of citizenship had its roots in ancient Greek and Rome and showed great change and development in the modern age when nation-states rose. Many states were affected by this process of change and development of this concept. Turkey that transformed from empire to nation-state also had to adapt itself to these changes. So, the Republic of Turkey attached crucial importance to citizenship education based on the experience from the period of the Ottoman Empire. Thus, the Turkish Republic benefited from educational practices to gain citizens common citizenship identity. This function of education remains valid today. This study aimed to reveal prospective social studies teachers’ metaphors regarding citizenship which has an important place in social studies education and the basis of citizenship education. A total of 139 prospective social studies teachers, studying at a state university in the Western Black Sea region of Turkey in the 2017-2018 academic year, voluntarily participated in the study. The phenomenological method, one of the qualitative research methods, was used. The data were collected by asking the prospective teachers: "Citizen(ship) is like/looks like…..…….. Because..............". The data were analyzed by content analysis. The prospective social studies teachers’ metaphors regarding the concept of citizenship were a flower, family, water, tree, sun, breath, earth, vein, ant, society, light, mineral, oxygen, seed.